Examining the Relations of the Home Literacy Environments of Families of Low SES with Children's Early Literacy Skills. Issue 2 (3rd April 2019) - Burris, Pamela W.; Phillips, Beth M.; Lonigan, Christopher J.
Abstract: This study examined variability of the home literacy environment (HLE) using multiple measures among families of low SES. The relations of the measures to each other and to children's early oral language skills and print knowledge were reported. Considerable variability of the self-reported HLE items and the Children's Title Checklist (CTC) but low correlations were found among items. Children's expressive language skills were predicted by the CTC. The number of storybooks in the home predicted variance within children's receptive vocabulary. Concepts about Print (CAP) scores were predicted by the primary caregivers' frequency of shared reading and the age when parents began reading to children. Children's letter name scores were not associated with any of the HLE measures in this study. The research provides additional information about the HLE within the homes of low SES using multiple measures and how they relate differentially to children's early language and literacy skills.